2012
DOI: 10.1071/wf10116
|View full text |Cite
|
Sign up to set email alerts
|

Linking complex forest fuel structure and fire behaviour at fine scales

Abstract: Improved fire management of savannas and open woodlands requires better understanding of the fundamental connection between fuel heterogeneity, variation in fire behaviour and the influence of fire variation on vegetation feedbacks. In this study, we introduce a novel approach to predicting fire behaviour at the submetre scale, including measurements of forest understorey fuels using ground-based LIDAR (light detection and ranging) coupled with infrared thermography for recording precise fire temperatures. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 28 publications
4
85
0
Order By: Relevance
“…If heterogeneity in fire behavior translates to heterogeneous fire effects, as seems likely from some detailed studies [80,81], then aggregated fuel patterns should lead to greater diversity in subsequent regeneration and growth patterns, a critical aspect of forest resilience [14,79]. Additionally, our hypothesis of increased sensitivity to aggregated fuel patterns under less severe conditions, if correct, bolsters the idea that greater fine-scale heterogeneity in fire behavior should result with lower wind speeds or less active surface fuels.…”
Section: Discussionsupporting
confidence: 50%
“…If heterogeneity in fire behavior translates to heterogeneous fire effects, as seems likely from some detailed studies [80,81], then aggregated fuel patterns should lead to greater diversity in subsequent regeneration and growth patterns, a critical aspect of forest resilience [14,79]. Additionally, our hypothesis of increased sensitivity to aggregated fuel patterns under less severe conditions, if correct, bolsters the idea that greater fine-scale heterogeneity in fire behavior should result with lower wind speeds or less active surface fuels.…”
Section: Discussionsupporting
confidence: 50%
“…Also, it does not provide a 3D biomass distribution. Calibration of TLS has also been used for fuel and fire effect characterization [25][26][27][28], but never in the past for leaf biomass estimation at plot scale.…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory fuel moisture desorption experiments, Kreye et al () found that turkey oak, southern red oak, post oak ( Q. stellate ), sand post oak, and white oak ( Q. alba ) approximated the drying response times of longleaf pine. The intricacies of litterfall, decomposition, and their interactions with the diversity of understory plants in longleaf pine ecosystems suggest that our understanding of effects of pyrophytic oaks on fire behavior in this ecosystem is still nascent (Hendricks et al , Loudermilk et al , Kreye et al ).…”
Section: Litter Fuels and Firementioning
confidence: 99%